Discursos de la nación en la Gaceta de Colombia - Garcés Hernández, Viviana; Botero Arango, Laura; Trujillo Rodríguez , Maritza Andrea; Múnera Restrepo, Alexánder (Folios, revista de la Facultad de Comunicaciones y Filología, 2023)
This article is part of a project that aims to index and map the newspaper collection of the Carlos Gaviria Díaz Library at Universidad de Antioquia as well as analyze a number of discourses on the nation that were published in two important newspapers: Gaceta de Colombia and Correo del Orinoco. This text focuses primarily on articles published in the Gaceta. The discourse of the nation revolved around two fronts of legitimacy, one internal and one external. The internal one was aimed to encourage the inhabitants of the territory to respect and legitimate the emergent national setting. The external legitimization aimed to gain recognition and respect from those who ruled “the civilized world” in order to strengthen its international status and economy.